Peningkatan Penguasaan Kosakata Bahasa Indonesia Melalui Media Gambar Di SDN Rawa Badak Utara 07 Pagi - Rukiah, Siti (Universitas Cokroaminoto Yogyakarta, 2023)
This study examines the Improvement of Indonesian Vocabulary Mastery Through Picture Media in Class II of SDN Rawa Badak Utara 07 Pagi. The results of the study show that the results of learning Indonesian through the media of images are able to involve intellectual, social and emotional abilities in an integrated manner so as to raise the potential for students to stimulate analytical thinking, be able to work together, and be able to solve problems independently. Students enjoy learning more and participate in learning with enthusiasm and enthusiasm and joy, so that the expected learning outcomes can be achieved. Learning by using image media can improve Indonesian learning outcomes. This is evidenced by the analysis of the first cycle with student learning outcomes of 67.25% and 72.00% in cycle II. Although the results in cycles I and II have increased, they have not reached the target set. Then the action of cycle III was carried out and the learning result was 76.25%. The learning outcomes in cycle III have exceeded the specified target of 75%. Thus it can be concluded that media images are able to improve the learning outcomes of Indonesian language students in class II of SDN Rawa Badak Utara 07 Pagi.